DEVELOPMENT OF SCIENCE LEARNING DEVICES ORIENTED ESD ON ENVIRONMENTAL POLLUTION MATERIALS TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS AND ENVIRONMENTAL LITERACY - Tahmid; Nur khoiri; M. Syaiful Hayat (LPPM Universitas PGRI Semarang, 2024)
This research aims to develop Education for Sustainable Development (ESD)-oriented science learning tools on environmental pollution material to improve critical thinking skills and environmental literacy for junior high school students. This research is development research (R&D) using a 4D model which includes the define, design, develop and disseminate stages. The tools developed consist of Teaching Modules, Student Worksheets, learning media, and evaluation instruments. Expert validation results show the device is feasible with an average score of 4.2/5. In a limited trial at SMP Negeri 2 Bojong Tegal, the implementation of the Teaching Module was 89%, 81% of students were actively involved, 87% gave positive responses. There was an increase in students' critical thinking skills (average 80.2) and environmental literacy (average 84.5). Success was supported by the application of the ESD approach with project learning, case studies, group discussions, and contextual-interactive media. Implementation of the Independent Curriculum with Teaching Modules and ATP increases student learning independence. The constraints of limited time and inadequate facilities were overcome by efficient time management and teacher creativity. Overall, the tools are valid, practical, effective, in accordance with the Independent Curriculum and 21st century learning with high-level thinking skills, environmental literacy and learning technology.